Proceso atención de enfermería en paciente de 26 años de edad por histerectomía abdominal. - Mullo Caluña, Guisela Magaly (2022)
Abdominal hysterectomy is based on a surgical procedure that is very recurrent in the hospital environment today. Among the first causes that can give way to consider this procedure are uterine leiomyoma, uterine fibroma, among others we can also find ectopic pregnancy. Cervical pregnancy is among the less common cases within the types of ectopic pregnancy. The risk that this type of implantation entails, since it is not diagnosed in time, can cause a serious hemorrhagic process. The development of this study focuses on the realization of a nursing care process applied to a 26-year-old patient who underwent surgery for an abdominal hysterectomy due to a cervical ectopic pregnancy, this patient presents a clinical picture of 3 days of evolution characterized by transvaginal bleeding in moderate quantity with the presence of clots after having presented a period of 7 weeks of amenorrhea, abdominal pain in the hypogastrium of mild intensity, transvaginal ultrasound traces the pelvic cavity, which shows the presence of an ectopic pregnancy implanted in the cervical region, this procedure confirms the diagnosis, so the corresponding procedure is carried out to improve its clinical condition. The nursing care process serves as a key tool to address each of the alterations present in the patient identified through the assessment of the 11 functional patterns of Marjory Gordon, each of these alterations will be classified in the diagnosis made by the patient, which will carry out the necessary interventions to recover the integrity of this patient.